2015
DOI: 10.5539/jms.v5n1p50
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Capital on Job Embeddedness and Organizational Cynicism: A Study on Menoufia University Hospitals

Abstract: Purpose: The objective of this study was to provide empirical evidence on the relationships between Psychological Capital (PsyCap), Job Embeddedness (JE) and Organizational Cynicism (OC).Research Design/Methodology: Using Luthans, 2006 of PsyCap, the study develops a number of hypotheses and tests them. Out of the 338 questionnaires that were distributed to employees at Menoufia University hospitals in Egypt, 315 usable questionnaires were returned, a response rate of 93%. Findings:The results showed that PsyC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 84 publications
1
13
1
1
Order By: Relevance
“…The hypotheses regarding with mediation roles of PsyCap and employee voice in the relationship between organizational justice and organizational cynicism were not supported. This finding is not in line with the argument based on broaden-built theory and previous findings (e.g., Chiaburu et al, 2013;Nafei, 2015) stating that perceiving fairness, dignity, accuracy and the right to participate in decision-making processes decrease cynicism as increasing employees' psychological resources.…”
Section: Conclusion Discussion and Suggestionscontrasting
confidence: 95%
See 1 more Smart Citation
“…The hypotheses regarding with mediation roles of PsyCap and employee voice in the relationship between organizational justice and organizational cynicism were not supported. This finding is not in line with the argument based on broaden-built theory and previous findings (e.g., Chiaburu et al, 2013;Nafei, 2015) stating that perceiving fairness, dignity, accuracy and the right to participate in decision-making processes decrease cynicism as increasing employees' psychological resources.…”
Section: Conclusion Discussion and Suggestionscontrasting
confidence: 95%
“…Moreover, previous studies reveal that there is significant negative relationship between PsyCap and organizational cynicism; as the PsyCap increases, organizational cynicism decreases (Avey, Luthans, & Jensen, 2009;. When employee perceives fairness, dignity, accuracy and the right to participate in decisionmaking process, her/his PsyCap resources, which are affected by work/organizational environment, augment, then this augmented resources decrease organizational cynicism (Avey, Wernsing, & F. Luthans , 2008;Chiaburu et al, 2013;Nafei, 2015;Çalışkan, 2014;Lather & Kaur, 2015). Thus, based on broaden-built theory and empirical findings, it is suggested that perceived organizational justice influences psychological capital, which in turn impacts cynicism.…”
Section: Psychological Capital and Employee Voice As Mediatormentioning
confidence: 96%
“…Şanlı [47] analyzed the relationship between job embeddedness and employee advocacy, organizational support and intention to quit the job. Nafei [46] analyzed the relationship between job embeddedness and organizational cynicism. Crossley, Bennett, Jex and Burnfield [19] and Şanlı [47] analyzed the relationship between the job embeddedness teachers and their intention to quit the job.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, there are also studies examining the relationship between the job embeddedness of academicians and their performance and burnout [42], organizational cynicism and work performance [43] in educational institutions. There are studies on job embeddedness in different institutions, as well [3,8,19,21,44,45,46,47]. When the literature is reviewed, even though the literature presents more studies conducted on belonging and the rate of studies carried out on belonging especially in educational institutions is remarkable [48], the literature presents a limited number of studies on vocational belonging [49, 50 51, 52, 53, 25].…”
Section: Vocational Belongingmentioning
confidence: 99%
“…Another empirical finding is the joint effects of psychological capital components have a positive impact on work outcomes like job embeddedness (Nafei, 2015). The finding points out that well-engaged employees would be better embedded.…”
Section: Theoretical Implicationsmentioning
confidence: 97%